Fretting-corrosion behavior of electroless Ni-P/Ni-P-TiO2 coatings obtained on AZ91D magnesium alloy by a chromium-free process (2020)
Ni-P electroless coatings are widely applied for protection of magnesium alloys and other materials due to the low energy consumption of the process and high resistance to corrosion and wear, properties that can be improved with the incorporation of particulate materials. Despite the attractive combination of properties of electroless coatings, studies in the tribocorrosion field, such as fretting-corrosion behavior of Ni-P electroless coatings, are very scarce. In this work, Ni–P-TiO2 composite electroless coatings with several variations on particles size and content applied on AZ91D magnesium alloys were analyzed under fretting-corrosion conditions in 3.5 wt.% NaCl. Coatings were obtained by direct electroless technique in multiple steps. Procedures were chromium-free and no activation pretreatment was needed. The tests were carried out using a fretting-corrosion tribometer from where open circuit potential and coefficient of friction were analyzed, as well as wear tracks on coatings surfaces were observed by SEM. The results obtained indicate that an improvement in the tribochemical behavior of Ni-P coatings can be achieved with the TiO2 codeposit, which modify the contact between body and counter body, the elastic accommodation and the dissipation of energy in the contact area